African swine fever virus evasion of host defences - Dixon, L.K. (Virus Res, 2019)
African swine fever virus causes a haemorrhagic fever in domestic pigs and wild boar. The continuing spread in Africa, Europe and Asia threatens the global pig industry. The lack of a vaccine limits disease control. To underpin rational strategies for vaccine development improved knowledge is needed of how the virus interacts with and modulates the host’s responses to infection. The virus long double-stranded DNA genome codes for more than 160 proteins of which many are non-essential for replication in cells but can have important roles in evading the host’s defences. Here we review knowledge of the pathways targeted by ASFV and the mechanisms by which these are inhibited. The impact of deleting single or multiple ASFV genes on virus replication in cells and infection in pigs is summarised providing information on strategies for rational development of modified live vaccines.